Comparative Analysis of Government Communication Strategies in Environmental Law Enforcement: A Case Study of Indonesia (DKI Jakarta) and Singapore - Ayuningrum, Wulandari Marcelyna; Herari, Noprita (Journal of Communication and Public Relations, 2024)
This study explores the communication strategies of Indonesia and Singapore in enforcing environmental law, particularly in the context of the Awyu and Moi tribes' refusal to give up their customary forests for palm oil plantations. Using a descriptive-comparative qualitative method, it highlights the differences in the two countries' environmental legal frameworks and communication approaches. With a low Environmental Performance Index (EPI) rating, Indonesia struggles with bureaucratic challenges in implementing its environmental laws, based on the 1945 Constitution and the 2009 Law on Environmental Protection and Management (UUPPLH). In contrast, Singapore ranked fourth globally for environmental quality, uses a common law system and specific legislation, such as the Environmental Protection and Management Act, with specialized regulatory agencies ensuring effective law enforcement and communication. Based on the WHO Strategic Communications Framework, the analysis reveals that Indonesia faces infrastructure and internet access issues and a lack of coordination between community initiatives and the central government. Conversely, Singapore effectively uses technology and media to spread environmental information, supported by well-structured community programs and strong government support. The study emphasizes the crucial role of strategic communication in enforcing environmental law and the need for Indonesia to streamline its law enforcement and improve its communication strategies for better environmental protection.